‘Letter’ and ‘Spirit’: the Foundation of Pauline Ethics - Westerholm, Stephen (New Testament studies, 1984)
The letter-spirit antithesis occurs in only three verses in the Pauline corpus: in Rom. 2. 29 (but note also v. 27), 7. 6, and 2 Cor. 3. 6. Nonetheless, it has traditionally been assigned a significance out of all proportion to its meagre textual base. Nor is this tendency difficult to account for: in terms so concise and memorable that they have passed into common speech, the antithesis captures a principle of manifest importance. Furthermore, those terms are sufficiently ambiguous (especially when separated from their original context) to allow thinkers of widely different views1 to see in them an expression of favourite themes of their own, and thus to lend to the latter the sanction of St Paul. Naturally, this leaves the exegete with the thankless task of remarking, ‘Very interesting – but not exactly what the apostle had in mind!’